Illustrated Story Book Media to Improve Reading Skills in Indonesian Language Learning for Second Grade of Elementary School Students - Nanditasari, Kadek Dwi; Wibawa, I Made Citra (Jurnal Pedagogi dan Pembelajaran, 2024)
Students' ability to read is still low. This is because there is no interactive supporting media available, only books which are dominated by lots of writing. This research aims to prove the effectiveness of picture story book media in Indonesian language learning to improve the reading ability of second grade elementary school students. This type of research is development. The model used is ADDIE which consists of five stages, namely analysis, design, development, implementation and evaluation. The subjects in this research were 17 class II students. The data collection method uses a questionnaire and evaluates oral reading ability. The instruments used were questionnaires and tests. The data analysis techniques used are qualitative descriptive analysis, quantitative and inferential statistics. The results of the research show a significance value (2-tailed) of 0.000 in the t-test so that it is concluded that the picture story book media for improving reading skills in class II students' Indonesian language learning is suitable for use as a learning medium in the learning process. The implication of this research is that it can be an example for teachers in using interactive media in learning to improve students' reading skills.